Attitudes of students of the Faculty of Physical Education towards exercise Some sports at Yarmouk University - ابوعاقوله, كرم; خلف ذيابات (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aimed to identify the attitudes of the students of the Faculty of Physical Education towards the practice of some sports at Yarmouk University. The researchers used the descriptive approach due to its suitability to the nature and objectives of the study. After the researchers were briefed on the theoretical literature and previous studies related to the topic of the current study, the researchers modified and developed the study tool of each of Al-Zahrawi’s study (2018), Al-Zoubi’s study (2017), and Abu Anza and Shamroukh’s study (2011). The current study population consisted of students from the Faculty of Physical Education at Yarmouk University who are registered for the course of football and athletics, and their number is (1022) male and female students, while the study sample amounted to (237) male and female students. To process the data statistically, the researchers used the spss statistical analysis program through the use of several calculations (arithmetical means, standard deviations, Cronbach alpha, t-test, one-way analysis of variance test), The results showed that the attitudes of the students of the Faculty of Physical Education towards the practice of some sports were to a high degree. The results also showed that there are statistically significant differences according to the gender variable in the psychological axis and in favor of females, while the results showed that there are differences according to the game variable in the axis (sports excellence, psychological, beauty and expression) and in favor of the football game. The results also showed statistically significant differences according to the year variable in the axis (health and physical fitness) in favor of the fourth year, the axis (athletic excellence) in favor of the first year, and the axis (beauty and expression) in favor of the first and second years. The researchers recommend investing in students' positive attitudes to spread awareness and interest in other sports and encourage them to practice them.